Katecheza w ponowoczesności – przestrzenie dialogu = Catechesis in Postmodernity – the Scope for Dialogue - Frejusz, Kamilla (Verbum vitae, 2024)
Catechesis is always context-and-time-specific. It cannot be detached from reality, nor can it ignore the problems experienced by those being catechised. In this sense, postmodernity and its characteristic secularism place catechesis in a situation that requires recognition, and then discernment, of how in this new reality it is possible to proclaim catechesis and to reach the contemporary person with the Gospel. This article undertakes a reflection on the possibilities of catechetical dialogue with individuals living in postmodernity characterised by secularisation. The analysis addresses two principal issues. First, the context is described in which contemporary dialogue is conducted within the broadly understood catechesis. Then, specific points of convergence are identified that may open up a meeting space necessary for the emergence of dialogue with the postmodern person. The article concludes with a critical summary.